PELATIHAN PEMBUATAN DOKUMEN PROSEDUR OPERSIONAL BAKU PADA UD. GALARASA - Susilo, Tegar Heru; Hananto, Valentinus Roby; Maulana, Yoppy Mirza (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2017)
UD. Galarasa is a home industry engaged in the production of snacks with its main product, "Kacang Aneh". The company’s vision is to provide healthy snack products to be consumed by the public. Healthy that is correspond to the Minister of Health standards through P-IRT certification, and halal standards that is correspond to LPPOM MUI through Halal certifications. Healthy and halal certification process can be easily done if the company has standard operating procedure (SOP). Activities used in this IbM are create training modules, provide training, and gives assignments in accordance with the needs of the document and business processes. This training is able to change the behavior of individuals and organizations process refers to food quality and safety, and is able to improve individual insights of modern corporate management in accordance with the quality management system.